Comparison of fine needle aspiration cytology and cell block to formal histology of small subcutaneous mass lesions in children. a prospective study at Red Cross War Memorial Children`s Hospital - Kunfaa Jnr, Ernest Naanwin-IB (Division of General Surgery, 2025)
Background Fine-needle aspiration cytology (FNAC) has been widely accepted as a safe, cost-effective and accurate tool for the preoperative diagnosis of masses or lesions in adults with over 90% accuracy. The use of FNAC with adjunct Cell block in children is still not widely accepted. Cell block technique refers to the processing of sediments, blood clots, or grossly visible tissue fragments from FNAB cytological specimens into paraffin blocks cut and stained as for formal histopathology. Use of Cell blocks as an adjunct to routine cytology smears can increase the sensitivity to a considerable extent leading to increased diagnostic yield. Excision, incision or core biopsy and formal histology is the gold standard to diagnose pathological causes of small, palpable masses in children. Problems related to this approach include the need for preoperative admission, starvation, a general anaesthetic, an operative procedure, postoperative pain, higher costs, as well as time taken for results, while FNAC can be performed as an outpatient procedure with local anaesthetic if needed. Objective This study aims to primarily determine the accuracy of the combination of FNAC and Cell block in comparison to gold standard histopathological diagnosis for mass lesions in children. Methods This is a prospective single center study involving children who had both FNAC and excision or incision biopsy taken at the same operative time for histological diagnosis at Red Cross War Memorial Children's Hospital (RCWMCH). Different pathologists assessed the FNAC/Cell block samples and the formal histological samples in different laboratory areas, thus ensuring blinding of the results. Results Fifty sets of samples were acquired from 49 nine participants, 29(59%) males and 20(41%) females. The age range was 17 days to 192 months, Pain 20(40%) was the most common presenting symptom, followed by fever 11(22%). The average duration of the lesions was 5 months (range 1 to 12 months). The average length of stay was 1 day (range 0 to 15 days). The head and neck 35(70%) were the most common site, followed by the axilla 5(10%). On formal histology there were 40(80%) benign lesions and 10(20%) malignant lesions. Nine patients had either bloody or inadequate FNAC samples, the Cell block was also bloody in 6 of these but gave the correct diagnosis in the other 3. The most common benign lesions were reactive lymph nodes 15(30%) and active mycobacterial infection 10(20%) whilst Hodgkin's Lymphoma 4(8%) was the most diagnosed malignancy. Five FNAC/Cell block combinations were falsely reported as reactive nodes, 3 of these represented Hodgkin's lymphoma on formal histology. When analysing the ability of FNAC and Cell block combination to differentiate between benign and malignant lesions (as opposed to achieving the full histological diagnosis), 30 out of 35 sample sets correctly diagnosed benign conditions giving an 85.7% concordance. The sensitivity and specificity of FNAC and Cell block combination to correctly diagnose benign lesions is 97.1% and 66.7% respectively, with a positive and negative predictive value of 91.9% and 85.6% respectively. For Malignant lesions 6 out of 9 sample sets correlated with the correct malignant diagnosis a concordance of 67%. The sensitivity and specificity of the FNAC Cell block combination to diagnose a malignant lesion was calculated at 66.6% and 97.1% respectively with a positive and negative predictive value of 85.6 and 91.9% respectively. The combination of FNAC and Cell block gave the correct histological diagnosis in 36 (72%) of patients. Limitations Single-center study and a small sample size. Conclusions FNAB is gradually being accepted as a diagnostic tool in the paediatric population. Cell block processing adds to the diagnostic potential of the FNAB. In this study, the FNAC Cell block combination showed an 85.7% concordance for benign conditions and 67% for malignant conditions when compared with formal histology. In the absence of a bloody tap, inadequate sample or necrosis, and excluding samples with a diagnosis of a reactive node which would prompt further assessment, 98% of patients undergoing FNAC and Cell block were correctly diagnosed with pathology that was confirmed on formal histology. The combination of FNAC and Cell block is a reliable method of diagnosing the histopathological diagnosis and in this series would have halved the number of patients needing a general anaesthetic to acquire a sample for formal histology. This represents a large saving in costs and theatre time, with the added advantage of patient safety.